ANALISIS HUKUM ATAS JUAL BELI DIBAWAH TANGAN YANG DILEGALISASI, STUDI ATAS PUTUSAN NOMOR : 467/PDT.G/2010/PN.MDN - SURYANI SURYANI (PREMISE LAW JURNAL, 2016)
A notary as a public official is required to comply not only with legal provision, but also with his professional ethics because without it his professional dignity will be no use. Based on the Ruling of Medan District Court 467/PDT.G/2010/PN.MDN between Mr. HS (capital owner, plaintiff) and Mr. DL (defendant, contractor), beginning with cooperative agreement: Mr. HS and Mr. DL bought a plot of land from Mr. X in which the trade was done before a notary based on a purchase contract and Power of Attorney, Mr. DL (defendant I, Contractor) as the buyer, but all costs of buying the land were paid by Mr. HS (plaintiff, Capital owner). The problem of this research were as follows: the responsibility of the parties concerned in the case of underhanded purchased contract, legal force of the legalized underhanded purchase contract, and the responsibility of the notary/PPAT (Official Empowered to Draw Up Land Deeds) to keep the original certificate safe in the certificate distributions. Keywords: Legalized Underhanded Purchase Contract